Transgenerational Epigenetic Inheritance of Traumatic Experience in Mammals - Švorcová, Jana (Genes, 2023)
In recent years, we have seen an increasing amount of evidence pointing to the existence of a non-genetic heredity of the effects of events such as separation from parents, threat to life, or other traumatising experiences such as famine. This heredity is often mediated by epigenetic regulations of gene expression and may be transferred even across several generations. In this review, we focus on studies which involve transgenerational epigenetic inheritance (TEI), with a short detour to intergenerational studies focused on the inheritance of trauma or stressful experiences. The reviewed studies show a plethora of universal changes which stress exposure initiates on multiple levels of organisation ranging from hormonal production and the hypothalamic-pituitary-adrenal (HPA) axis modulation all the way to cognition, behaviour, or propensity to certain psychiatric or metabolic disorders. This review will also provide an overview of relevant methodology and difficulties linked to implementation of epigenetic studies. A better understanding of these processes may help us elucidate the evolutionary pathways which are at work in the course of emergence of the diseases and disorders associated with exposure to trauma, either direct or in a previous generation.
Keywords: trauma; Heredity; transgenerational epigenetic inheritance; Inheritance Patterns; epigeneze genetická; DNA methylation; savci; databáze genetické; Databases, Genetic; typy dědičnosti; Animals; RNA; Mammals; stress; zvířata; HPA axis; Epigenesis, Genetic; dědičnost